International actors and the formation of laws - Karjalainen, Katja; Tornberg, Iina; Pursiainen, Aleksi (Springer, 2022)
This open access book addresses the discourse that creates, modifies, and reshapes the law, as well as discourse participants. The book focuses on the actors operating in legal regimes and their subtly, bluntly, or even outright aggressive impact on the formation of laws. As the book examines the intersection of domestic, European, international, and even transnational, legal regimes where new law emerges as a product of this discourse, it contributes to the understanding of the mobility of law and contemporary law's interactive nature. This book provides enlightening examples of diverse legal fields influenced by international, non-domestic actors. It covers a wide range of relevant topics, from financial sanctions to the rights of Indigenous peoples, and addresses actors ranging from the European Union and the European Court of Human Rights to disability organizations. By exploring actors, the book stresses their objectives and driving forces behind their efforts to influence law. The book reveals an array of diverging methods used by international actors to influence law. Additionally, the book resonates with Nordic legal tradition and highlights Nordic commitment to rule of law and equality. The authors are members of the Finnish branch of the International Law Association (ILA) and recognized experts in their particular fields and have been afforded freedom to adopt the approach they perceive as best suited to their topic. The book is aimed at a broad range of readers involved in academic research and study; lawyers working in government departments, international organizations, or private practice with an international focus; as well as policy makers and influencers in international organizations, government bodies, and non-governmental organizations.